'A trail of derision and denunciation'? Anglican–Nonconformist relationships in the East Midlands during and after the First World War. (3rd July 2017) - Bell, Stuart
Abstract : While discussions of religious activity during the First World War have commonly stressed the development of ecumenical relationships and much has been made of the Appeal to All Christian People made by the 1920 Lambeth Conference of Anglican bishops, little attempt has been made to examine the reality of local ecumenical activity in the opening decades of the 20 th century. Some evidence, such as that referenced in the title, has suggested that the animosity of the previous century continued. Conversely, much anecdotal war-time evidence from both military and civilian contexts indicates a thawing of previous attitudes. This article closely examines the evidence from the east midlands, drawing the conclusion that ecumenical relationships were generally neither antagonistic nor genuinely friendly. Rather, Anglicanism and nonconformity largely existed in separate social and cultural worlds, and there is little evidence indicative of significant local ecumenical progress in that period.